Analysis of Communication Privacy on Instagram - Anwar, Alfiansyah (Jurnal Kajian Manajemen Dakwah, 2023)
The problem in this research is related to the analysis of privacy communication on Instagram. The purpose of this study was to find out the results of the analysis of articles in journals. In this study used qualitative methods. The results of the analysis show that the research in the first article obtained the fact that this situation still occurs among high school students in Yogyakarta. Research in article 2 obtained three out of five informants indicating that this feature allows them to reveal stories that are too personal